Study of the process $$e^+e^- → η π ^0γ $$ e + e - → η π 0 γ in the energy range $$\sqrt{s} = {1.05-2.00}$$ s = 1.05 - 2.00 GeV with the SND detector - M. N. Achasov; A. Yu. Barnyakov; A. A. Baykov; K. I. Beloborodov; A. V. Berdyugin; D. E. Berkaev; A. G. Bogdanchikov; A. A. Botov; T. V. Dimova; V. P. Druzhinin; V. B. Golubev; A. N. Kirpotin; et al. (European Physical Journal C: Particles and Fields, 2020)
Abstract The process $$e^+e^-→ η π ^0γ $$ e + e - → η π 0 γ is studied in the center-of-mass energy range 1.05–2.00 GeV using data with an integrated luminosity of 94.5 $$\hbox {pb}^{-1}$$ pb - 1 collected by the SND detector at the VEPP-2000 $$e^{+}e^{-}$$ e + e - collider. The $$e^+e^-→ η π ^0γ $$ e + e - → η π 0 γ cross section is measured for the first time. It is shown that the dominant mechanism of this reaction is the transition through the $$ω η $$ ω η intermediate state. The measured cross section of the subprocess $$e^+e^-→ ω η → η π ^0γ $$ e + e - → ω η → η π 0 γ is consistent with previous measurements in the $$e^+e^-→ π ^+π ^-π ^0η $$ e + e - → π + π - π 0 η mode. It is found, with a significance of $$5.6σ $$ 5.6 σ , that the process $$e^+e^-→ η π ^0γ $$ e + e - → η π 0 γ is not completely described by hadronic vector-pseudoscalar intermediate states. The cross section of this missing contribution, which can originate from radiation processes, e. g. $$e^+e^-→ a_{0}(1450)γ $$ e + e - → a 0 ( 1450 ) γ , is measured. It is found to be 15–20 pb in the wide energy range from 1.3 to 1.9 GeV.